Teeth category classification via seven‐layer deep convolutional neural network with max pooling and global average pooling. Issue 4 (21st May 2019) - Li, Zhi; Wang, Shui‐Hua; Fan, Rui‐Rui; Cao, Gang; Zhang, Yu‐Dong; Guo, Ting
Abstract: Accurately classify teeth category is important in further dental diagnosis. Analyzing huge dental data, that is, identifying the teeth category, is often a hard task. Current automatic methods are based on computer vision and deep learning approaches. In this study, we aimed to classify the teeth category into four classes: incisor, canine, premolar, and molar. Cone beam computed tomography was used to collect the data. We proposed a seven‐layer deep convolutional neural network with global average pooling to identify teeth category. Data augmentation method was used to enlarge the size of training dataset. The results showed the sensitivities of incisor, canine, premolar, and molar teeth are 88%, 86%, 84%, and 90%, respectively. The average sensitivity is 87.0%. We validated max pooling gives better results than average pooling. Our method is better than three state‐of‐the‐art approaches.